2013
DOI: 10.1021/es401791s
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt Pathway Mediates Nrf2/ARE Activation in Human L02 Hepatocytes Exposed to Low-Concentration HBCDs

Abstract: We investigated the effects of hexabromocyclododecanes (HBCDs) at environmentally relevant concentrations on human L02 hepatocytes and explored possible underlying molecular mechanism(s), focusing on functional interactions between the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and nuclear factor-erythroid 2-related factor 2/antioxidant response element (Nrf2/ARE) pathways. The results showed that low concentrations of HBCDs could stimulate cell proliferation in a "DNA-dependent protein kinase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…In addition, Akt activation is closely associated with the induction of antioxidant effects through Nrf2 activation. The inhibition of PI3K leads to the reduction of Nrf2 activation, resulting in a decrease in HO-1 expression (35,36). Our results are consistent with these studies, in that the expression of Nrf2 and HO-1 was augmented by PME in unstimulated RAW 264.7 cells.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Akt activation is closely associated with the induction of antioxidant effects through Nrf2 activation. The inhibition of PI3K leads to the reduction of Nrf2 activation, resulting in a decrease in HO-1 expression (35,36). Our results are consistent with these studies, in that the expression of Nrf2 and HO-1 was augmented by PME in unstimulated RAW 264.7 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Previous study showed that activation of Nrf2 could active FXR . And PI3K/Akt pathway could regulate the activation of Nrf2 in some different types of cells . However, we could not rule out other transcription factors potentially involved in curcumin effects, since curcumin, as a naturally occurring compound, has been thought to target at multiple signaling pathways and numbers of transcription factors.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, increased PERK basal activity in Nck1-deficient MIN6 cells may directly promote constitutive Nrf2 activation mediating cell survival to oxidative damage. On the other hand, silencing Nck1 may also decrease MIN6 cells susceptibility to death induced by oxidative stress through PI3K-Akt activation of Nrf2, a prosurvival mechanism in response to oxidative stress [65,66]. Akt activation in MIN6 cells depleted of Nck1 may result from the inhibition of the mTORC1-dependent negative feedback loop leading to PI3K inhibition since mTORC1 activity was attenuated in these cells.…”
Section: Discussionmentioning
confidence: 99%